DEVELOPMENT OF AN ALTERNATIVE LOW-COST LANDSLIDE MONITORING METHOD USING DATA FROM TUSAGA-AKTIF GNSS NETWORK - BAYRAK, TEMEL; EYO, ETIM; BAŞOĞLU, NEŞAT; MUSA, TAJUL; AKPEE, DINEBARI (Boletim de Ciências Geodésicas, 2015)
The main objectives of this paper are to develop a kinematic deformation analysis model for landslides using Kalman filtering procedures; and to utilise the observations from TUSAGA-Aktif GNSS Network in Turkey to determine the velocity fields of a landslide study area in the Eastern Black Sea Region of Turkey. Thirty five (35) points were established for the determination of 3-D time dependent velocities of the landslides study area. Point displacements and velocities were determined by single point kinematic model to perform 3-D statistical analysis, and to assess the significance of point displacements and velocities using three periodic observations from TUSAGA-Aktif Network. The determined velocities were used to generate the velocity fields of the landslide area for three epochs using Geographic Information System (GIS). The results obtained indicate that almost all the monitored points showed significant movements, with varying magnitudes of velocities. The directions of movement of the 35 monitored points were also determined. The results show that the dominant trends of landslide movements in the study area are in the northwest and northeast directions. These results are in agreement with the previous results obtained in the same study area about ten years ago.